2019
DOI: 10.4103/ijp.ijp_237_17
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of topical mupirocin versus mupirocin with sucralfate combination in chronic skin ulcers

Abstract: OBJECTIVES:The objective of this study was to carry out a head-to-head comparison of topical sucralfate combined with mupirocin versus mupirocin alone in the treatment of chronic skin ulcers with respect to both effectiveness and safety.MATERIALS AND METHODS:A parallel-group, open-label, randomized, controlled trial (CTRI/2015/12/006443) was carried out with patients suffering from skin ulcers of Wagner grading 1 or 2 persisting for over 4 weeks. Ninety-six patients were recruited in total, and the modified in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…SCF is employed in the treatment of different gastrointestinal diseases to reduce inflammation of the epithelial surface and favor the healing process 18 . SCF join tightly to the inflamed mucosa, forming a stable and insoluble layer that protect damaged epithelium 20,21 . SCF improves the healing of inflamed mucosa, has an antioxidant and anti-inflammatory properties, and stimulates the production of EGF [18][19][20][21][22][23][24] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SCF is employed in the treatment of different gastrointestinal diseases to reduce inflammation of the epithelial surface and favor the healing process 18 . SCF join tightly to the inflamed mucosa, forming a stable and insoluble layer that protect damaged epithelium 20,21 . SCF improves the healing of inflamed mucosa, has an antioxidant and anti-inflammatory properties, and stimulates the production of EGF [18][19][20][21][22][23][24] .…”
Section: Discussionmentioning
confidence: 99%
“…SCF join tightly to the inflamed mucosa, forming a stable and insoluble layer that protect damaged epithelium 20,21 . SCF improves the healing of inflamed mucosa, has an antioxidant and anti-inflammatory properties, and stimulates the production of EGF [18][19][20][21][22][23][24] . Authors who evaluated the effects of SCF using models of chemically-induced colitis have shown that the application of clysters with SCF increases mucosal repair, probably through increasing mucus production, which favors epithelial healing 31,32 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the antibacterial efficacy of MUP was enhanced by combing with topical sucralfate in contrast to MUP alone. The results revealed that the skin ulcer area was reduced significantly in the combination treatment [92]. In another study, antimicrobial activity against S. aureus, MUP alone, or both in combination with any of monoterpenes, such as thymol, menthol, and 1,8-cineole, was tested.…”
Section: Miscellaneousmentioning
confidence: 99%
“…O SCF vem sendo empregado há décadas no tratamento de diferentes doenças gastrointestinais com o objetivo de reduzir a inflamação da superfície epitelial e favorecer o processo de cicatrização 73 . O SCF, possui uma alta capacidade adesiva juntando-se firmemente às erosões da mucosa inflamada, formando uma camada estável e insolúvel que recobre o epitélio danificado 74,75 . O SCF melhora a cicatrização da mucosa inflamada por estimular a produção do fator de crescimento epitelial, aumenta a redução de muco pelas células do epitélio do trato gastrointestinal, além de apresentar…”
Section: Fonte: Figura Da Autoraunclassified